Restoration and Management of a Degraded Baldcypress Swamp and Freshwater Marsh in Coastal Louisiana - Rachael G. Hunter (Water, 2016)
The Central Wetlands Unit (CWU), covering 12,000 hectares in St. Bernard and Orleans Parishes, Louisiana, was once a healthy baldcypress–water tupelo swamp and fresh and low salinity marsh before construction of levees isolated the region from Mississippi River floodwaters. Construction of the Mississippi River Gulf Outlet (MRGO), which funneled saltwater inland from the Gulf of Mexico, resulted in a drastic ecosystem change and caused mortality of almost all trees and low salinity marsh, but closure of the MRGO has led to decreases in soil and surface water salinity. Currently, the area is open water, brackish marsh, and remnant baldcypress stands. We measured hydrology, soils, water and sediment chemistry, vegetation composition and productivity, accretion, and soil strength to determine relative health of the wetlands. Vegetation species richness is low and above- and belowground biomass is up to 50% lower than a healthy marsh. Soil strength and bulk density are low over much of the area. A baldcypress wetland remains near a stormwater pumping station that also has received treated municipal effluent for about four decades. Based on the current health of the CWU, three restoration approaches are recommended, including: (1) mineral sediment input to increase elevation and soil strength; (2) nutrient-rich fresh water to increase productivity and buffer salinity; and (3) planting of freshwater forests, along with fresh and low salinity herbaceous vegetation.